From Trust to Action: Navigating the Mediating Role of Attitudinal Loyalty between OCSE and Impulsive Buying Behavior - Rayhan Ananda Irawan; Mike Yolanda (Journal of Educational Management Research, 2026)
The rapid growth of e-commerce in Indonesia has increased platform competition, yet the impact of Online Customer Shopping Experience (OCSE) on impulsive buying remains unclear. This study explores the influence of functional and psychological dimensions of OCSE on impulsive buying behavior, considering the mediating effect of attitudinal loyalty and the moderating role of self-control. Method: A quantitative causal research design was used, with data collected from 120 respondents via a survey. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Functional OCSE (e.g., ease of navigation, informativeness) does not significantly affect attitudinal loyalty or impulsive buying. However, psychological OCSE (e.g., trust, comfort, enjoyment) significantly influences both attitudinal loyalty and impulsive buying. Attitudinal loyalty mediates the relationship between psychological OCSE and impulsive buying, but not the functional pathway. Self-control has a weak and insignificant moderating effect. This study enhances the understanding of OCSE by distinguishing its functional and psychological dimensions. For educational management, the findings suggest that improving the psychological experience on e-learning platforms can increase student engagement, strengthen loyalty, and enhance participation, contributing to more effective learning outcomes.